Seed oil content and fatty acid profiles of five Euphorbiaceae species from arid regions in Argentina with potential as biodiesel source - Aranda Rickert, Adriana Marina (2011)
Five Euphorbiaceae species (Jatropha macrocarpa, J. hieronymi, J. excisa, Cnidoscolus tubulosus and Manihot guaranitica) were analysed for seed oil content and fatty acid profiles in order to evaluate their potential as sources of biodiesel. The five species are perennial shrubs adapted to arid and semi-arid environments of north-western Argentina. The seed oil content for all species ranged from 27.9 to 38.7% by dry weight. Fatty acid composition consisted mainly of linolenic, myristic, palmitic, stearic, arachidic, oleic and linoleic acids, with linoleic and oleic acid being the most abundant. Among the five species analysed, J. macrocarpa has the best potential to be used as a biodiesel source. The average total seed oil content (35.8%) and a high value of oleic acid (27.3%) together with the lowest values of linoleic acid (55.8%) make this species a promising crop as a source of biodiesel in arid and semi-arid regions.